THE MODEL OF FREE SPREADING A FLOW RAPID BEHIND A RECTANGULAR PIPE - Olga Burtseva; Viktor Kohanenko; Sergey Evtushenko; Maria Alexandrova (International Journal for Computational Civil and Structural Engineering, 2022)
The article considers the free spreading of a turbulent stationary two-dimensional open potential water flow into a wide diverting riverbed behind a non-pressure pipe of a rectangular section. A system of nonlinear partial differential equations of motion has been adopted as the mathematical model of the flow in the physical plane. When moving to the plane of the velocity hodograph, the nonlinear system of equations is transformed into a linear system with respect to partial derivatives. Using the obtained system of equations, various problems along the flow of two-dimensional water streams have been solved analytically. The paper determines the flow kinetics parameter t and the angle q characterizing the direction of the local flow velocity vector at the intersection points of an arbitrary equipotential and an arbitrary current line. The X, Y coordinates of these points are found. The peculiarities of changing the angle θ during the transition of the vertical front of the XD are taken into account.